Institutional erosion and new strategies: Changing contexts for learning in agriculture in Northern Sweden - Waldenström, Cecilia (2023)
This article describes the erosion of institutions that support farmers' learning and the construction of knowledge in agriculture in an area of agricultural decline. It is based on a qualitative study in northern Sweden, exploring farmers' learning to farm, their peer networks, contacts with advisory services and their sales relationships. As farming is increasingly differentiated, with an intensification of production in some areas and increasing farmland abandonment in others, so are the institutions that support farmers' learning. Farmers handle this in different ways, and the article indicates that resourceful farmers, dependent on farm income, seek out and create contexts for learning. Others seem increasingly decoupled from advisory institutions and upstream industries, selling their produce in local networks. The article illustrates that the widening gap in agrarian production is related to a differentiation of social and institutional preconditions for the construction of knowledge in farming.